Effects of pre-processing methods of pili nuts (Canarium ovatum Engl.) on its nutritional and mineral bioavailability - Millena, Cristopher G.; Cañaveral, Nicole Ivy P.; Colanza, Lyza B.; Señora, Tonnette Ashley G.; Tarog, Joana Marie V.; Enovejas, Sherlyn M.; Renovalles, Kristine Mae A.; Ruivivar, Sylvester S.; Germination (2023)
Pili nut is an emerging tree nut among other well-known nuts in the world. It is endemic in the Bicol Region, Philippines. Pre-processing of nuts such as soaking in brine or activation and germination enhances their nutritional quality; however, no scientific substantiation is available to support this claim. Thus, the present study aimed to determine the effects of preprocessing techniques and assess their effects on the nutritional, mineral bioavailability, and antinutritional components. The techniques were: [1] activation through soaking in salt solution (with and without testa) and [2] germination (pre-sprouted and sprouted). The proximate composition reveals that pre-processing pili nuts reduces the fat; the same applies to protein, except for soaking with testa. For total macrominerals, soaking increases the level of Na, with the highest levels in those without testa (2984 mg kg–1) and with testa (553 mg kg–1). The level of total Mg was reduced. For total trace elements, pre-processing does not affect the amount of Zn. Necessary control is recommended when selecting salt as a raw material during processing due to the increase in the levels of Cd and Pb after soaking in brine. For mineral bioavailability, treatments do not affect the available K (p = 0.074) and Mn (p = 0.15). Pre-processing has a negative impact on the bioavailability of Fe. Soaking without testa reduces the phytic acid, whereas germination reduces both tannic and phytic acid. The present research reveals that pili nuts pre-processed through soaking and germination have varying effects on the levels of antinutrients, total minerals, and bioavailability.
Keywords: Pili nut; Nutritional value of food; Germination